1978
DOI: 10.1056/nejm197809072991002
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Function in Essential Thrombocythemia

Abstract: Platelets from two patients with essential thrombocythemia failed to aggregate or release serotonin in response to concentrations of epinephrine that aggregated platelets from normal controls. Therefore, we studied their alpha-adrenergic receptors, using 3H-dihydroergocryptine (3H-DHE), an alpha-adrenergic antagonist. These platelets contained an average (mean +/- S.E.) of 210 +/- 18 and 227 +/- 27 3H-DHE binding sites per platelet--less than half that found on control platelets, 464 +/- 37 (P less than 0.01).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

1981
1981
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(18 citation statements)
references
References 20 publications
1
16
0
1
Order By: Relevance
“…Absent or decreased platelet aggregability to epinephrine has been known to be a feature of myeloproliferative disorders, and this abnormality provides information that helps to differentiate platelet neoplastic proliferation from reactive production [1, 2]. A depressed responsiveness to epinephrine in platelets from healthy subjects has been sporadically reported [3, 4]; however, epidemiological studies on this abnormality in the broader population are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Absent or decreased platelet aggregability to epinephrine has been known to be a feature of myeloproliferative disorders, and this abnormality provides information that helps to differentiate platelet neoplastic proliferation from reactive production [1, 2]. A depressed responsiveness to epinephrine in platelets from healthy subjects has been sporadically reported [3, 4]; however, epidemiological studies on this abnormality in the broader population are limited.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the copy number of platelet surface P2Y 12 receptors may be decreased in MPN patient platelets just like the α-2b adrenergic receptors [6]. Alternatively, storage pool deficiency, which is well characterized in some MPN patients [9,23] and which is associated with reduced or absent ADP-induced second wave aggregation in platelet aggregation tests with the light transmission method, may affect ADP-induced VASP phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of thrombosis is further increased in MPN patients bearing the JAK2 V617F mutation [1]. Abnormal platelet function is found in a significant proportion of MPN patients [3,4,5,6,7]. Studies done with platelet aggregation tests revealed that MPN platelets have an impaired response to various stimulants, mainly epinephrine and adenosine diphosphate (ADP).…”
Section: Introductionmentioning
confidence: 99%
“…aVWS is also associated with multiple myeloma [24][25][26][27][28][29], Waldenstrom macroglobulinaemia [30,31], chronic lymphocytic leukemia [32], hairy cell leukemia [33], and non-Hodgkin lymphoma [34][35][36]. Most cases of myeloproliferative disorders associated with aVWS are essential thrombocythemia [37][38][39][40][41][42][43][44][45][46][47], while polycythemia vera [48] and chronic myeloid leukemia [49][50][51] are less frequent. The second most common groups of disorders associated with aVWS is neoplasia, including Wilms tumors [52][53][54][55][56][57] and carcinomas [58,59], followed by immunological diseases, most notably SLE [14,60,61] and hypothyroidism [62][63][64][65][66][67][68]…”
Section: Associated Disorders and Pathogenic Mechanismsmentioning
confidence: 99%